Simulation model of resources allocation of container terminals - Tan Ming Kuan, Jessica; Mat Tahar, Razman (Universiti Utara Malaysia, 2004)
A large amount of capital is invested in developing container terminals in order to cope with the growth of trade and, at the same time, to increase the level of efficiency. Managing a container terminal becomes a difficult and challenging task due to its complexity. Simulation model has the potential of being extremely useful in assessing and analyzing different strategies in the planning and management of the terminal. The simulation model is also useful for forecasting the likely effects on system performance of any physical and policy changes. In this study an efficient simulation model for container terminal planning is developed. The model assists in making informed decisions 0n the logistic management of terminal operations and the optimal utilization of resources.